Independence of helicopter rotor derivatives under non-uniformity of induced velocity distribution at low forward speed - Bryce, W. W. (College of Aeronautics, Cranfield, 1956)
A radial parabolic induced velocity distribution agreeing closely with flight measurements has been used for the hovering case. Continues...